Reading John 11:1-45 from a post-normal times perspective - J. Thomaskutty (Acta Theologica)
This article re-reads John 11:1-45 in light of post-normal times. It analyses aspects such as 4Ss, 3Cs, and 3Ts, in order to expound on the Johannine community situation and to understand the paradigmatic significance of John’s narrative artistry within the contemporary context. The study elaborates on the speed with which the narrative evelops from John 11:1-45; the scope of the story that extends from the local Bethany to universal realities; the scale of the story, as it changes directly between both the local and global situations, and the simultaneity of the event, as it initiates multiple interactions within the macronarrative framework. The article attempts to explore the complexities, chaotic situations, and contradictions embedded within the narrative master plan of the story. In order to suggest a new way forward, the narrator develops her/his arguments by focusing on the three tomorrows of the story, as s/he provides several narrative clues about the extended present, the familiar futures, and the unthought futures. Using hope as a significant hermeneutic key within the Johannine community context, the narrator elaborates on the community’s attempts to reframe their faith and praxes and their aspirations to embrace a new normal situation. The article concludes that the Johannine experience of a postnormal situation and the hope for a new normal can be considered a hermeneutic paradigm in the contemporary global scenario.